Infection With Helicobacter pylori Is Not a Major Independent Risk Factor for Stable Coronary Heart Disease: Lack of a Role of Cytotoxin-Associated Protein A–Positive Strains and Absence of a Systemic Inflammatory Response - Koenig, Wolfgang; Rothenbacher, Dietrich; Hoffmeister, Albrecht; Miller, Markus; Bode, Guenther; Adler, Guido; Hombach, Vinzenz; März, Winfried; Pepys, Mark B.; Brenner, Hermann (Circulation (New York, N.Y.), 1999)
Background —There is controversy about the association between Helicobacter pylori infection and manifestations of coronary heart disease (CHD), the potential role of the more virulent H pylori strains, and whether or not a positive serostatus is related to increased levels of markers of systemic inflammation. Methods and Results —We assessed the prevalence of an infection with H pylori and in particular the anti–cytotoxin-associated protein A (CagA) antibody response of the more virulent strains expressing CagA in 312 patients with stable CHD and in 479 control subjects. Serological prevalence of H pylori infection (IgG titer) was significantly higher in patients than in control subjects after adjustment for age and sex (44.2% versus 31.3%, P <0.001). After adjustment for various covariates in multiple logistic regression, the odds ratio (OR) for CHD was 1.3 (95% CI, 0.9 to 1.9) given a positive IgG serostatus. The prevalence of CagA-positive strains was 27.9% in patients and 21.7% in control subjects ( P =0.076 adjusted for age and sex). The OR for CHD in the fully adjusted model was 1.1 (95% CI, 0.7 to 1.7). None of the inflammatory markers (C-reactive protein, fibrinogen, plasma viscosity, or leukocytes) was significantly different according to serostatus. Conclusions —In this large case-control study, the association of H pylori infection with stable CHD was strongly reduced and was no longer statistically significant after controlling for potential confounders. We also found no independent association between the more virulent strains and CHD. In addition, a positive serostatus was not associated with a systemic inflammatory response. Thus, these data do not support the hypothesis that infection with H pylori might be a major risk factor for stable CHD.